PENGARUH HEDONIC SHOPPING MOTIVATION TERHADAP KEPUTUSAN BERKUNJUNG DI WISATA BELANJA KOTA BANDUNG (Survei Terhadap Wisatawan Nusantara yang Mengunjungi Kawasan Wisata Belanja Kota Bandung) - Susanti, Dian Febriana; Mulyadi, Hari (Universitas Pendidikan Indonesia, 2015)
Since the 2010 until 2012, the tourist shopper in Bandung continues to decline. One way to overcome this is to know the motivation of tourists, in order to create a strategy that fits with tourist. The government must be aware of the changes the tourist motivation, tourists are now no longer oriented to the economy and stuff, but they are shifting toward emotional orientation. In marketing this is called hedonic shopping motivation. Hedonic shopping motivation is an encouragement for someone to do the shopping, where these activities lead to a positive emotional experiences in the form of excitement, and can provide a stimulus for someone sensory. This study aims to describe the hedonic shopping motivation and visiting decision, and know the effect of hedonic shopping motivation on the visiting decision in Bandung shopping area. The population in this study is the tourist who visited the shopping areas in Bandung. Sampling technique used is cluster random sampling, with 156 respondents. Data analysis technique used is multiple regressions. The results of a descriptive study showed the sub-variable of hedonic shopping motivation that get the highest rating is value shopping, the lowest is role shopping. The sub-variable of visiting decision that gets the highest rating is the amount of the purchase. The results of a verification study showed the simultaneous hedonic shopping motive has an influence on visiting decision. However, with partial test only gratification shopping hat has an influence on the visiting decision, while the other sub variables are no influences on visiting decision. Based on this research, shopping area managers should focus on strategies to improve the role shopping and the amount of the purchase.